PENGARUH SEMANGAT KERJA DAN KOMPENSASI SERTA KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN KANTOR PT. INSANI BARAPERKASA DI SAMARINDA - KHAFIIDU ROHMAN; YONATHAN PONGTULURAN; ARIESTA HEKSARINI (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2016)
The purpose of this study was to determine the influence of spirit of work  and compensation as well as organizational commitment on employee job performance. This research was conducted at the Office PT. Insani Baraperkasa  sampling method using census sampling, with director do not include the amount of the population used as many as 75 people and collected samples of 65 people who were in PT. Insani Baraperkasa. The data in this study using primary data, interviews and questionnaires. Hypothesis test used in this study is Multiple Linear Regression using SPSS version 22. The results of this study show that: 1) Spirit of work has a positive and significant effect on employee performance office at PT. Insani Baraperkasa, 2) Compensation has a positive and significant effect on employee performance office at PT. Insani Baraperkasa, 3) Organizational commitment has a positive and significant effect on employee performance office at PT. Insani Baraperkasa.Keywords: Spirit of work, compensastion, organizational commitment and performance.